KESENJANGAN HAK SOSIAL DAN HAK POLITIK: STUDI MENGENAI GELANDANGAN DI INDONESIA - Nurussyahadah, Syallika; Mafaza, Taqya; Azzahra, Bunga Indriani; Cindy; Putri, Andini Nathania; Kusuma, Ardli Johan (Cahaya Ilmu Bangsa, 2024)
This research aims to analyze how homeless people in Indonesia face gaps in obtaining their social and political rights using Kristian Stokke's political citizenship approach. Homeless people often experience marginalization that prevents them from accessing appropriate social services, as well as participating in the political process. As well as the inhibiting factors that cause this inequality will be discussed in this article, including structural barriers, inadequate regulations, and social stigma and government efforts to overcome the gap between homeless people, to understand whether these efforts are successful in fulfilling the politics of redistribution (welfare) and politics. representation (political participation) for homeless people. This research uses a qualitative approach method by applying descriptive analysis methods. This method was chosen because it is relevant to the research objective, namely to conduct an in-depth study of the gaps in social and political rights faced by homeless people in Indonesia. Data collection techniques are carried out by examining various sources of information, such as books, scientific articles, academic journals, official documents and reports related to the research topic being studied. Research findings show that the rights of homeless people as Indonesian citizens, such as civil, political and social rights, have not been fully fulfilled. Based on Kristian Stokke's political approach to citizenship, fulfilling these basic rights is a state obligation that should be guaranteed to every citizen. However, research findings show that the state's constitutional obligations have not been optimally implemented, even though various social policies have been pursued.